2010
DOI: 10.1243/09544070jauto1228
|View full text |Cite
|
Sign up to set email alerts
|

Robust design optimization of the McPherson suspension system with consideration of a bush compliance uncertainty

Abstract: A robust suspension system design optimization, which takes into account the kinematic behaviours influenced by bush compliance uncertainty, is presented. The design variables are the positions of the joints, and the random constant is the bush stiffness with uncertainty. The design goals for these kinematic behaviours are typically represented as deviations over the wheel movements. It can be very difficult to evaluate the analytical design sensitivity because the deviation is defined by using the maximum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Usually four to six design variables were chosen for optimization in previous studies. 20,21 In our study, to include more design variables in the optimization, design variables with the top 60% (9 of 15) overall sensitivity index values were selected from Table 3, which were damper upper y , control arm front z , control arm outer z , control arm outer y , control arm outer x , steering rod inner z , steering rod outer z , steering rod outer x , and steering rod inner x .…”
Section: Selection Of Design Variables and Uncertain Variablesmentioning
confidence: 99%
“…Usually four to six design variables were chosen for optimization in previous studies. 20,21 In our study, to include more design variables in the optimization, design variables with the top 60% (9 of 15) overall sensitivity index values were selected from Table 3, which were damper upper y , control arm front z , control arm outer z , control arm outer y , control arm outer x , steering rod inner z , steering rod outer z , steering rod outer x , and steering rod inner x .…”
Section: Selection Of Design Variables and Uncertain Variablesmentioning
confidence: 99%
“…Choi et al (2004) performed the reliability optimization design by SLSV method using the results of deterministic optimization as the initial value of the reliability based optimization design after using the design sensitivity which was applied by the finite difference method. Kang et al (2010) suggested the design method which maximized the functions of suspension system and minimized the deviation simultaneously by applying the robust design optimization based on meta-model to avoid the difficulties of design sensitivity analysis and numerical noise. Figure 1 is the typical design process of suspension system.…”
Section: Review Of Suspension System Designmentioning
confidence: 99%
“…either on the ride comfort or on the handling performance. [11][12][13][14][15] Therefore, in this paper, a new methodology is proposed specifically to address the problem of a large number design variables with conflicting design requirements. Regularity-model-based multi-objective estimation of the distribution algorithm (RM-MEDA) is employed to solve this problem to produce the Pareto front of an achievable set of solutions which is a compromise between the ride comfort and the handling performance.…”
Section: Introductionmentioning
confidence: 99%